Respuesta :

Answer:

Step-by-step explanation:

6 - 3(x + 1) = 18 ⇔ 3 - 3x = 18 ⇒ x = 5

y - 6 = 17 ⇒ y = 23

z - 3 = 4z ⇒ z = - 1

18 - 3(0) = 9w ⇒ w = 2

========================

I'm going to solve for you some another question you asked, I did not see the right answer...  :)

There are two scenarios, because the expression under the module can be positive and can be negative: | 3x + 2| - 2 > 3 ⇔  | 3x + 2| > 5

(1). If (3x + 2) is positive then

3x + 2 > 5 ⇒ x > 3

(2). If (3x + 2) is negative then

- (3x + 2) > 5

- 3x - 2 > 5

- 3x > 7 ⇒ x < - [tex]\frac{7}{3}[/tex]

The final answer is x < - 2.3 or x > 1

Ver imagen xenia168